Assessment of clinical and haematological profile in dengue fever - Salvi, Dhairya; Moradia, Dhanvi (International Journal of Research in Medical Sciences, 2020)
Introduction: Series of biochemical and haematological changes occur during the course of the illness. Physicians should be aware of the most common clinical as well as clinical and biochemical presentations which are important for the clinical management of patients and thus crucial for saving a life. Therefore, this study aimed to highlight the most common clinical features and biochemical findings of dengue cases. Methods: A total of 200 cases of suspected dengue fever were included in the study. The present is the prospective cohort study; samples were selected with sampling technique. A total of 200 cases of suspected dengue fever were included in the study. The frequency of various signs and symptoms and the values of laboratory tests were compared. The results were tabulated and correlated. Results: In our series in clinical manifestations, all cases presented with fever, myalgia was found in 156 patients, headache was found in 106 patients, rashes were present in 28 patients, others clinical features are nausea, pain abdomen was seen in 42 patients, loose motion was seen in 34 patients etc. None of our patient have visual complains. Retro-orbital pain was noted in 12 patients. Bleeding manifestations in any form was seen in 78 cases. Conclusions: Dengue needs to be suspected in any patient presenting with a short duration of fever and myalgia. Bleeding tendencies should be closely watched for. When features of plasma leakage such as pedal edema, pleural effusion, ascites, are present, patient should be closely watched for and should be immediately managed.